Mufassir Scientist's Criticism of the Sexual Orientation Deviations of the LGBT - Zaky Maulana Subhi; Andri Nirwana A. N (al-Afkar, Journal For Islamic Studies, 2024)
Human rights, particularly the freedom to live without discrimination, stand as the bedrock for constructing a just society. Within the context of LGBT, research underscores the detrimental impact of discrimination on the mental well-being of LGBT individuals. Freedom of expression, particularly for LGBT activists, is deemed a fundamental democratic right, allowing them to voice their identities without the fear of discrimination. From an Islamic perspective, the prohibition of LGBT is rooted in the concept of human fitrah, where heterosexual relationships are perceived as a form blessed by Allah. This prohibition is seen as an effort to preserve the order established by the Creator, in line with Islamic moral norms and the maintenance of moral equilibrium in society. The narratives of the Prophets, notably the story of Prophet Lut, serve as warnings against homosexual behavior, with the prohibition of LGBT regarded as a preventative measure to avert social and moral disasters. Muslims are reminded of their duties and responsibilities in attaining life's objectives, guided by an understanding of Allah's teachings regarding sexual relationships. This study employs a literature review method, focusing on Islamic theories, concepts, and literature. Data sources include the Quran, Al-Azhar Commentary, and various Indonesian commentaries. Data analysis is executed through a qualitative descriptive method, utilizing triangulation as a data collection technique. Research findings indicate that LGBT reflects cultural diversity based on sexual and gender identities. In Indonesia, perspectives on LGBT vary, with some supporting with restrictions, while others find it taboo and condemnatory. Discrimination and violence against LGBT persist, particularly in employment, housing, education, and health. From an Islamic viewpoint, LGBT is considered a deviation from fitrah and Allah's command, with a rejection of homosexual behavior in Islam. Despite ongoing debates, research indicates that the existence of LGBT triggers complex health and social issues. A holistic approach is imperative to address the negative impacts of LGBT, encompassing educational, social, and mental health aspects.